Glutamine/proline-rich PQE-1 proteins protect Caenorhabditis elegans neurons from huntingtin polyglutamine neurotoxicity - Faber, Peter W. (National Academy of Sciences, 2002)
Huntington's disease is a progressive neurodegenerative disease caused by a polyglutamine (polyQ) repeat expansion in the huntingtin protein [Huntington's Disease Collaborative Research Group (1993) Cell 72, 971–983]. To understand the mechanism by which polyQ repeats cause neurodegeneration and cell death, we modeled polyQ neurotoxicity in Caenorhabditis elegans. In our model, expression of N-terminal fragments of human huntingtin causes polyQ-dependent degeneration of neurons. We conducted a genetic screen to identify proteins that protect neurons from the toxic effects of expanded polyQ tracts. Loss of polyQenhancer-1 (pqe-1) gene function strongly and specifically exacerbates neurodegeneration and cell death, whereas overexpression of a pqe-1 cDNA protects C. elegans neurons from the toxic effects of expanded huntingtin fragments. A glutamine/proline-rich domain, along with a charged domain, is critical for PQE-1 protein function. Analysis of pqe-1 suggests that proteins exist that specifically protect neurons from the toxic effects of expanded polyQ disease proteins.